Colon and rectal cancer in Ibadan, Nigeria: an update (2010)
Introduction Colorectal cancer was hitherto a rarity in the rural African in general and in Nigerians inclusive. Ibadan is a sprawling city in Western Nigeria with a population of about 2.5 million inhabitants. Lately, several publications from surgeons in this city have alluded to an increase in the number of colorectal cancer cases managed in the teaching hospital. Objectives To examine the incidence of this disease over 10 years in order to confirm or exclude the apparent significant increase in colorectal cancer cases in Ibadan, Nigeria. Method This is a retrospective study highlighting the age, sex, clinical features, operations performed and histopathological subtypes of patients who had surgery for colorectal cancer in the University College Hospital Ibadan between July 1995 and August 2004. Results Two and sixty-eight patients were seen over 10 years. The male: female ratio was 1.16:1. The mean age was 41 years and the peak age was the 51- to 60-years group. Fourteen per cent of the patients were 30 years and below. Sixty-two per cent of the patients had rectal carcinoma while 33.2% had colonic carcinoma. Around 60.7% of colonic lesions were right-sided. The most common histopathological subtype was adenocarcinoma (78.8%), mucinous adenocarcinoma was 10.8% and signet ring type was 2.6%. Conclusion Colorectal cancer is a disease on the increase in Ibadan. The mean age of 41 years is much lower than in the Western world. The male: female ratio still favours male patients slightly. About one in seven patients are 30 years and below. Adenomatous polyps were absent in the resected specimens.